Association of triglyceride glucose-body mass index with non-small cell lung cancer risk: A case-control study on Chinese adults - Feifei Wang; Ting He; Guoliang Wang; Tuo Han; Zhongqiang Yao (Frontiers in Nutrition, 2022)
Background and objectivesInsulin resistance (IR) is closely related to non-small-cell lung cancer (NSCLC) risk. Recently, triglyceride glucose-body mass index (TyG-BMI) has been recognized as one of the simple indexes of insulin resistance (IR). However, there are limited data on the relationship between TyG-BMI and NSCLC. Here, we investigated the association of TyG-BMI with NSCLC risk in Chinese adults.MethodsThis study consisted of 477 NSCLC cases and 954 healthy subjects. All participants were enrolled from 3201 Hospital affiliated to the Medical Department of Xi’an Jiaotong University. TyG-BMI was calculated based on the values of fasting blood glucose, triglyceride, and BMI. The association of TyG-BMI with NSCLC risk was estimated by logistic regression analysis.ResultsThe mean value of TyG-BMI was statistically increased in patients with NSCLC compared to the control group (201.11 ± 28.18 vs. 174 ± 23.78, P < 0.01). There was a significant positive association between TyG-BMI and NSCLC (OR = 1.014; 95% CI 1.007–1.021; P < 0.001) after controlling for confounding factors. Moreover, the prevalence of NSCLC was significantly elevated in participants in the high TyG-BMI tertiles than those in the intermediate and low TyG-BMI tertiles (60.46% vs. 12.61% vs. 26.83%, P < 0.01). Importantly, TyG-BMI achieved a significant diagnostic accuracy for NSCLC, with an AUC (area under the curve) of 0.769 and a cutoff value of 184.87.ConclusionThe findings suggest that TyG-BMI is a useful tool for assessing NSCLC risk. Thus, it is essential to follow up on high TyG-BMI, and lifestyle modification is needed to prevent NSCLC in people with high TyG-BMI.